Analisis Simbol Abjad pada Anak Tunarungu Kategori Sibi Disekolah Luar Biasa (SLB) Negeri 1 Watampone ( Kajian Semiotika Charles Sanders Pierce): Penelitian - Rasma; Irna Fitriana; Andi Srimularahmah (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study analyzes the use of alphabetic symbols among deaf children who use SIBI (Indonesian Sign System) at Sekolah Luar Biasa (Special Needs School) Negeri 1 Watampone, using the semiotic theory of Charles Sanders Peirce. The aim of this research is to understand how deaf children interpret and produce alphabetic symbols within the context of classroom learning. Peirce's semiotic theory, which divides signs into three main elements—representamen, object, and interpretant—is used to analyze this visual communication process. A qualitative method was employed in this study, with data collected through direct observation and interviews with teachers and students. The findings indicate that the use of alphabetic symbols in SIBI not only aids in language learning but also plays a role in the development of cognitive and communication skills in deaf children. Furthermore, the study found that the interpretation of alphabetic symbols by deaf children is strongly influenced by their learning context and individual experiences. Therefore, the use of SIBI has proven effective in supporting the communication needs of deaf children at SLB Negeri 1 Watampone.